Las estrategias metodológicas en el aprendizaje de Ciencias Naturales en la Unidad Educativa Mariano Negrete. - Cruz Acosta, Gladys Viviana (2021)
This research is focused in the existing problem at the Unidad Educativa Mariano Negrete, where there is a lack of application of innovative methodological strategies for the learning of Natural Sciences, by teachers, which has caused the disinterest and the lack of motivation in students towards an active and reflexive learning of the Natural Sciences, which implies the learning about the world that surrounds them, the interaction with it and its care. To improve this process, the development of a strategy for learning Natural Sciences is proposed. The research was developed with a qualitative – quantitative approach, where surveys and personal dialogues were used to know about the diagnosis of the situation of the learning strategies for Natural Sciences used by teachers from the Unidad Educativa Mariano Negrete, which results have allowed us to know the little knowledge and use of the innovative methodological strategies. After the application of the proposal an improvement of the motivation, participation and performance of the students could be evidenced, for this, it was concluded that the proposal will contribute significantly to the improvement of the learning of Natural Sciences in the institution.